GAMBARAN PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA ANAK KELAS IV DI SD 1 DEMAK IJO - Dahlia Putri Gantina; Suharjono Suharjono; Sutrisno Sutrisno (Journal of Oral Health Care, 2017)
Oral health is an important factor in human life. Maintaining oral health is very important to get our body's health, especially in children, because in childhood is very important because the condition of milk teeth (dental decidui) today will determine the state of permanent teeth replacement. One cause one to overlook dental and mouth health problems are factors of knowledge about oral hygiene is lacking. Knowledge of parents is very important in the formation of the underlying behaviors that support or do not support children's dental and oral hygiene .. This study aims to reveal the knowledge of oral health in children fourth grade N 1 Demak Ijo. This research is descriptive analytic. Respondents were selected with a total sampling method with sample number equal to the population of 66 people. The tools used in this study was a questionnaire containing about oral health knowledge. The results showed 52 (78.78%) had a good knowledge of the level of knowledge of oral health. Conclusions: The majority of respondents have a good knowledge about the level of knowledge of oral health and about more than half of respondents have a dental and oral hygiene status was good.